ECONOMIC AND GEOGRAPHICAL LOCATION OF URBAN SETTLEMENTS AS DEVEL-OPMENT FACTORS (USING THE TERMEZ DISTRICT AS AN EXAMPLE) (Scientific journal of the Fergana State University, 2026)
The article provides a detailed analysis of the urbanization process in the Termiz district of Surkhandarya region. In particular, it examines the formation of settlements in the district, their economic, social, and cultural development, as well as the connection between the settlements’ locations and the geographical features and natural resources. Furthermore, the article discusses the main factors affecting the development of settlements - transport routes, water resources, agricultural and industrial capacities, population density, and the historical and strategic position of the district - and demonstrates how these factors influence the urbanization process.